Pelatihan Penelitian Tindakan Kelas bagi Guru SD - Zulfadewina Zulfadewina; Roslaini Roslaini; Septi Fitri Meilana (BADAN PENERBIT STIEPARI PRESS, 2023)
This Community Service was carried out at Pondok Ranggon 04 Pagi Elementary School. Partner problems, namely: Teachers do not understand to find a focus on problems in PTK, Teachers are not yet motivated in making scientific work, especially in class action research, Teachers have not designed PTK Proposals properly and correctly. Solutions to partner problems namely: Providing delivery of material to teachers about Classroom Action Research (PTK), Providing assistance to teachers regarding the study of Classroom Action Research (PTK) proposals that have been made by teachers as an effort to improve teacher abilities, Increase teacher understanding and motivation in designing work scientific especially in Classroom Action Research. The planned community service activities are carried out in two online days and one offline day in the form of training using lecture methods, demonstrations and practice of writing PTK proposals as an effort to improve teacher abilities. The stages of implementing community service that will be carried out are as follows: Preparation Stages, Implementation Stages, Monitoring and Evaluation Stages, Publications, PKM Reports, Post Program Follow-ups.